Strategi Komunikasi Piapi Animation Dalam Membangun Brand Image Melalui Instagram Sebagai Studio Animasi Pertama Di Sumatera Barat - Mahalia Zahra; Ria Edlina (CV. ITTC INDONESIA, 2025)
Piapi Animation or PT Creative Media is the first animation studio in West Sumatra which is located in Padang City. This research was conducted to find out the steps of marketing communication strategies carried out by Piapi Animation in building brand image in the province of Sumatera Barat. In a business environment that continues to grow and compete, it is important for creative industry companies to understand the important role of brand image in achieving their marketing goals. The method used is a qualitative research method with descriptive data type. The data collection techniques used are observation, interviews, and documentation. The results of the research using the AIDA theory by E. St. Elmo Lewis, namely Attention, Interest, Desire, Action, Piapi animation strives to be more active in disseminating content in the Attention aspect, Piapi introduces the world of animation to the audience through content. Meanwhile, in the Interest and Desire aspects, the existence of interesting content makes people want to follow the @piapianimation Instagram account. The last aspect is Action, the audience starts watching the animation that has been created by subscribing to Durioo + or downloading the Durioo+ application.